MENA Economic and Development Prospects 2013 : Investing in Turbulent Times - Ianchovichina, Elena; Devarajan, Shantayanan; Burger, Martijn (World Bank, Washington, DC, 2014)
The political and social upheavals that followed the Arab Spring of 2011 continue to dominate economic activity and near term prospects in the Middle East and North Africa (MENA). Although political transitions bring promises of greater political and economic freedom, in MENA the process remains far from complete and has been accompanied by increased political and macroeconomic instability in 2013. In Egypt, rising social and political tensions weighed heavily on confidence. In Syria, a marked escalation of the civil war exacted a heavy economic and human toll, with spillovers to neighboring Lebanon, Jordan, and Iraq. Oil production in developing MENA oil exporters has fallen because of security setbacks, infrastructure problems, strikes, and in the case of Iran, economic sanctions. The outlook for 2013-and more so for 2014, is uncertain and subject to a variety of risks, mostly domestic in nature and linked to political instability, while global economic conditions have become more favorable. In 2013, economic growth is expected to remain weak or weaken relative to 2012 across MENA and average 2.8 percent, down from the estimated 5.6 percent in 2012. Growth has been most volatile in the MENA's developing oil exporting countries, and is projected to slow down considerably due to unfavorable developments, especially in Libya, Iran, and Syria. Some aspects of instability, including the quality and stability of government institutions and policies, did play a role, but others, such as democratic accountability, did not. Furthermore, Foreign Trade Investment (FDI) flows to the resource intensive and non-tradable sectors appear immune to political instability, but FDI flows to the tradable sectors exhibit a clear negative response.